1997
DOI: 10.1038/sj.sc.3100355
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment of chronic constipation in paraplegic subjects

Abstract: Chronic constipation is the main gastrointestinal complaint of spinal cord injury (SCI) patients, and has a signi®cant e ect on patients' lives, concerning nursing dependence, morbidity and complications. Many therapies have been proposed to treat chronic severe constipation, most of them with limited e ect or being unpredictable in their e ect or being expensive or very radical. Ten spinal cord injury patients have been submitted to a therapeutic protocol based on a high residue diet, a standardised water int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 16 publications
1
23
0
4
Order By: Relevance
“…12,13 However, the samples in these previous studies were younger and injured for a shorter time. Increasing age and duration of injury are associated with increased use of medicated rectal stimulants, manual evacuation and oral laxatives; 3 response to less invasive BM techniques may be reduced as time since injury increases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…12,13 However, the samples in these previous studies were younger and injured for a shorter time. Increasing age and duration of injury are associated with increased use of medicated rectal stimulants, manual evacuation and oral laxatives; 3 response to less invasive BM techniques may be reduced as time since injury increases.…”
Section: Discussionmentioning
confidence: 92%
“…12,13 was developed. Interventions were ordered from the least to most invasive to allow assessment of both effect of each intervention and effects of combined interventions, while ensuring effective BM.…”
Section: Intervention Groupmentioning
confidence: 99%
“…There is Level 4 evidence (from three pre-post studies; aggregate N ¼ 65) [16][17][18] that multifaceted bowel management programs reduce GI transit time, incidences of difficult evaluations, and duration of time required for bowel management ( 18 recently modified the bowel management program originally proposed by Badiali et al 16 by including an additional step of manual evacuation and found a significant decrease in the number of bowel movement episodes requiring laxatives (from 62.8 to 23.1%). These authors also reported a significant decrease in the mean duration of bowel management episodes with the introduction of this protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Dicult Intestinal Evacuation (DIE) 2,27 is de®ned when two or more of the following are present: (a) Defecatory frequency of less than three times a week; 7 (b) Hard stools. These cause urgency, dicult bowel evacuation, and sensation of incomplete evacuation; 7,10 (c) Prolonged intestinal management time, more than 45 min.…”
Section: Methodsmentioning
confidence: 99%